Assessing the Enforcement of Sexual Harassment Policies in Learning Institutions in Uganda. Challenges, Progress and Recommendations - Isabella Adong (Uganda Christian University, 2024)
Sexual Harassment is defined as behaviour characterized by the making of unwelcome and inappropriate sexual remarks or physical advances in a workplace or other professional or social situation. Sexual Harassment is a pervasive problem in education that affects both the learning Institution's integrity as well as students’ confidence who fall victim to it. Sexual Harassment is, however, a small section of a broader term called sexual violence. This research looks at the different laws that expressly provide for sexual harassment: international laws, domestic laws, and learning institutional policies. This dissertation looks at the various challenges facing the enforcement of these sexual harassment policies in learning institutions in Uganda, as well as the various things adopted to improve the enforcement of these policies. This dissertation employs various methodology which include use of questionnaire and assessing literature. I will also critique various existing literature on sexual harassment enforcement.